Crystal Engineering with Multipoint Halogen Bonding: Double Two‐Point Donors and Acceptors at Work - Bulfield, David (Chemistry, 2020)
The combination of singly or doubly bidentate halogen‐bond donors with double bidentate acceptors was investigated as a supramolecular synthon in crystal engineering. The crystal topologies obtained feature novel halogen‐bonding motifs like double two‐point recognition and infinite chains or networks based on two‐point interactions. Induced conformational changes in the double bidentate halogen‐bond donors could be exploited to obtain different 1D and 2D networks. All solid‐state studies were accompanied by DFT calculations to predict and rationalize the outcome.